2013
DOI: 10.3109/13880209.2013.814692
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors ofα-glucosidase andα-amylase fromCyperus rotundus

Abstract: Context: A methanol extract of Cyperus rotundus L. (Cyperaceae) rhizomes showed inhibitory activity against a-glucosidase and a-amylase, two enzymes involve in carbohydrate digestion. Objective: Identification of compounds from C. rotundus rhizomes responsible for the inhibition of a-glucosidase and a-amylase. Materials and methods: Compounds were identified by a phytochemical investigation using combined chromatographic and spectroscopic methods. a-glucosidase and a-amylase inhibitory activities were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…The porcine pancreas α -amylase (A3176, Sigma-Aldrich) enzyme inhibitory activity was carried out according to the standard method with minor modifications [2022]. The substrate was prepared by boiling 100 mg potato starch in 5 mL phosphate buffer (pH 7.0) for 5 min and then cooling to room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The porcine pancreas α -amylase (A3176, Sigma-Aldrich) enzyme inhibitory activity was carried out according to the standard method with minor modifications [2022]. The substrate was prepared by boiling 100 mg potato starch in 5 mL phosphate buffer (pH 7.0) for 5 min and then cooling to room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, constituent 1 has β-secretase and Aβ inhibitory activities ( Jeon et al ., 2007 ; Rivière et al ., 2010 ; Richard et al ., 2011 ), but the direct neuroprotective effects of constituent 1 were demonstrated for the first time in the present study. Several studies have reported that constituent 2 exhibits anti-oxidative, anti-diabetic, and anti-photoaging activities, as well as vasorelaxing effects ( Kobayashi et al ., 2006 ; Sano et al ., 2011 ; Maruki-Uchida et al ., 2013 ; Tran et al ., 2014 ), while no study on the neuroprotective effects of constituent 2 has been reported. However, further investigation is necessary to confirm these effects in animal models and to determine the molecular mechanisms underlying the neuroprotection of constituents 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…This comparison is made with the anti-diabetic compound acarbose. The concentration of the test compound is 200 and 500mg/kg (Tran et al, 2014).…”
Section: Cyperus Rotundus (Scariosus) (Musta )mentioning
confidence: 99%